High Definition Archaeology: Threads Through the Past - Gowlett, John A., editor.
1 online resource
Keywords: "The use of modern analyses of high definition data is used to trace relationships or decision paths which could not have been seen with the techniques available 30 years ago. Examples are drawn from a variety of areas and periods."--Provided by publisher.